Auditoría en seguridad vial del sector La Victoria – Zarzal, entre la abscisa del km 36+000 a km 42+600 (2022)
In this document is the process carried out to carry out a road safety audit in the Abscisa section km 36 + 000 to km 42 + 600 of the La Victoria-zarzal road, taking into account variables of containment barriers, signaling, physical risks and aggressive behavior. It was decided to use the descriptive quantitative methodology, field visits were made, speed operations were carried out in order to carry out risk matrices and risk maps using tools such as an odometer and a speed radar that allowed generating conclusions and suggestions regarding the current state of the road, the frameworks are also explained: theoretical and conceptual used.